dupA+H. pylori reduces diversity of gastric microbiome and increases risk of erosive gastritis - Chen, Ruiyan; Li, Ying; Chen, Xiaodong; Chen, Jianhui; Song, Jie; Yang, Xiaoqiao; Ye, Lifang; Wu, Zizhong; Xie, Peng; Zhong, Qiong; Yang, Runshi; Wu, Jiachuan (Frontiers in Cellular and Infection Microbiology, 2023)
Helicobacter pylori is believed to induce gastropathy; however, the exact pathogenic molecules involved in this process have not been elucidated. Duodenal ulcer promoting gene A (DupA) is a virulence factor with a controversial role in gastric inflammation and carcinogenesis. To explore and confirm the function of DupA in gastropathy from the perspective of the microbiome, we investigated the microbial characteristics of 48 gastritis patients through 16S rRNA amplicon sequencing. In addition, we isolated 21 H. pylori strains from these patients and confirmed the expression of dupA using PCR and qRT-PCR. Bioinformatics analysis identified diversity loss and compositional changes as the key features of precancerous lesions in the stomach, and H. pylori was a characteristic microbe present in the stomach of the gastritis patients. Co-occurrence analysis revealed that H. pylori infection inhibits growth of other gastric inhabiting microbes, which weakened the degradation of xenobiotics. Further analysis showed that dupA+ H. pylori were absent in precancerous lesions and were more likely to appear in erosive gastritis, whereas dupA− H. pylori was highly abundant in precancerous lesions. The presence of dupA in H. pylori caused less disturbance to the gastric microbiome, maintaining the relatively richness of gastric microbiome. Overall, our findings suggest that high dupA expression in H. pylori is correlated with a high risk of erosive gastritis and a lower level of disturbance to the gastric microbiome, indicating that DupA should be considered a risk factor of erosive gastritis rather than gastric cancer.